Neo-soviet media model (Part 2) (Herald of Journalism, 2023)
In the previous issue of our scientific journal (Herald of KazNU, Journalism Series, No. 2 (68) 2023,pp. 16-28) the translation from English of the first part of Sarah Oates’s program article “The Neo-SovietMedia Model,” published in 2007 in the journal “Europe-Asia Studies” (Sarah Oates, 2007) was firstpresented to the readers.Also the “Foreword by the scientific editor of the translation, professor of National Research University“Higher School of Economics” in Moscow, S.G. Davydov was published. It contained deeperscientific understanding and a critical view at methodology of the research, as well as the theoretical andhistorical contexts of scientific discussions about normative media theories of the 2000s.In the current issue, readers are offered the translation of the second (final) part of Sarah Oates’sarticle, in which, according to the author’s annotation, “explores the genesis of the neo-Soviet mediamodel. Based on the results of the study of Russian media in the post-Soviet period, as well as a reviewof their activities during elections in the above region, the article concludes that Russian media currentlyoperate in a “neo-Soviet” manner. Factors shaping this media model include the rejection of a balancedapproach or objectivity; the presence of flaws in the legislation regulating the activities of the media;self-censorship; state interference and pressure on the media; lack of professionalism in the journalisticenvironment; and an atmosphere of violence against journalists. Furthermore, in the transition from theSoviet to the neo-Soviet model, there is continuity in how the media are perceived by their audience.”
Keywords: Sarah Oates, neo-Soviet media model, media system, censorship, post-Soviet space, content analysis.